Emotion, Morality, and Interpersonal Relations as Critical Components of Children’s Cultural Learning in Conjunction With Middle-Class Family Life in the United States - Sirota, Karen Gainer (Frontiers in Psychology, 2019)
An enduring question in the cultural study of psychological experience concerns how emotion may play a role in shaping moral aspects of children’s lives as they are mentored into socially preferred ways of understanding and responding to the world at hand. This article brings together approaches from psychological and linguistic anthropology to explore how cultural schemas of normativity are communicated, embodied, and enacted as children participate in day-to-day family activities and routines. Illustrative examples emanate from a videotaped corpus of naturalistic interactional data that document the daily lives of 32 ethnically diverse U.S. middle-class families who reside in the Los Angeles, California metropolitan region. The article employs discourse and narrative analysis to examine how children are apprenticed into perceiving, appraising, and reacting to the emotions of self and others as culturally shaped indicators for proper comportment. Data analysis emphasizes how implicit components of caregivers’ interactions with children (i.e., gesture, gaze, facial expression) intertwine with explicit, verbal communication to constitute intricately layered affective messages that shape the evaluative frames through which children interpret, display, and respond to emotions. The article identifies two culturally salient childrearing practices, “pep talks” and “time outs,” that apprentice children into moral accountable relationships with others by encouraging them to manage their emotions in culturally preferred ways. Study findings suggest that parental communications conveying praise and approval—or conversely indexing disapproval—towards children are emotionally resonant motivational practices in this cultural milieu as children are mentored into culturally meaningful emotional management techniques. The article highlights how children actively employ semiotic socio-communicative resources and it closely traces their sense-making processes in tandem with their discursive contributions to the moment-by-moment interaction. It argues that emotion, morality, and interpersonal relations are critical in shaping children’s acquisition of consensually validated ways of perceiving, feeling, and responding to the phenomena they encounter in their day-to-day lives. This perspective aims towards contextualized understandings that render plausible connections between local contexts of everyday action and broader macro-level discourses and master narratives, such as those associated with a neo-liberal emphasis on cultivating citizens who learn to regulate their emotions on behalf of self and others.